2013
DOI: 10.1002/nau.22551
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of urinary incontinence for post-stroke inpatients in Southern China

Abstract: The prevalence of UI among post-stroke inpatients is high. Stroke inpatients looked after by health care assistant, hemorrhagic stroke, mixed stroke, parietal lobe lesion, chronic cough, aphasia, and post-stroke depression were high-risk groups for UI. These patients should be targeted when planning intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
3
24
2
2
Order By: Relevance
“…Functional status, haemorrhagic stroke, aphasia, motor deficit, mental impairment and post-stroke depression have all been associated with the risk of developing UI. [1,2] Its prevalence ranges between 33% and 79% in the days following acute stroke with almost half of those patients remaining incontinent oneyear after stroke. [1,3] UI has been reported to be an independent predictor of institutionalization, severe disability, and death in the post-stroke period.…”
Section: Introductionmentioning
confidence: 99%
“…Functional status, haemorrhagic stroke, aphasia, motor deficit, mental impairment and post-stroke depression have all been associated with the risk of developing UI. [1,2] Its prevalence ranges between 33% and 79% in the days following acute stroke with almost half of those patients remaining incontinent oneyear after stroke. [1,3] UI has been reported to be an independent predictor of institutionalization, severe disability, and death in the post-stroke period.…”
Section: Introductionmentioning
confidence: 99%
“…Alterações neurológicas, decorrentes de um acidente vascular encefálico, são as que mais provocam quadros de incontinência urinária (CAI et al, 2015). A incontinência urinária é uma circunstância clínica comum após o acidente vascular encefálico, decorrendo da hiperreflexia ou hipo-reflexia da bexiga, distúrbios no controle do esfíncter e ou perda sensória (DUMOULIN; KORNER-BITENSKY;TANNENBAUM, 2007).…”
Section: Introductionunclassified
“…Estudo realizado em uma cidade da China por Cai et al (2015), com 711 pa cientes após acidente vascular encefálico, identificou prevalência de 44,3% de in continência urinária e os principais fatores de risco para incontinência associados com acidente vascular encefálico foram tipo de acidente vascular encefálico, lesão de lobo parietal, tosse crônica, afasia e depressão. Em um estudo realizado no Canadá por Pizzi et al (2014) em pacientes após acidente vascular encefálico isquêmico, foi evidenciada prevalência de incontinência urinária de 79%.…”
Section: Introductionunclassified
“…Among the situations that imply the clinical condition of urinary incontinence are neurological disorders, and among them, the observation of incontinence among stroke patients (5) . Regardless of the cause, stroke can alter brain structures responsible for controlling urination, thus compromising the urinary system (6) .…”
Section: Introductionmentioning
confidence: 99%
“…A study realized in a city in China with 711 patients after stroke identified prevalence of 44.3% of urinary incontinence, and the main risk factors for incontinence associated with stroke were the stroke, parietal lobe lesion, chronic cough, aphasia and post-stroke depression (5) . A study on patients after ischemic stroke showed a 79% prevalence of urinary incontinence (6) .…”
Section: Introductionmentioning
confidence: 99%